(untitled) (Sudurpaschim Spectrum, 2026)
This study focuses on the impact of human resource management (HRM) key practices on the retention of employees in hotel industry of Kathmandu. Four major dimensions of HRM training and development, career opportunities, work-life balance, and compensation and benefits were measured to know their impact on employees’ intentions to stay with their organizations. A quantitative research design was applied and data was gathered from 202 respondents using a structured questionnaire. Both the descriptive and inferential statistics were used, namely reliability testing, correlation analysis, and multiple regression analysis by using the software (SPSS 27). Reliability analysis confirmed the highest reliability of all measurement constructs with Cronbach’s Alpha values above 0.7. Descriptive statistics showed that hotel workforce in Kanchanpur is mostly young, unmarried and with a moderate level of education and working in frontline positions. Correlation analysis showed strong positive relationships between employee retention and three HRM factors - training and development, work-life balance and compensation and benefits. Regression results revealed that training and development (beta = 0.271, p = 0.001), work-life balance (beta = 0.323, p = 0.000), and compensation and benefits (beta = 0.373, p = 0.000) had significantly positive impact on employee retention while career opportunities (beta = 0.002, p = 0.948) was statistically insignificant. The model accounted for 87.3% variance in the retention of employees and has thus a good predictive power. The findings point out the necessity of structured training programs, supportive work-life balance policies, and competitive compensation packages in order to improve employee retention in the hotel industry in Kathmandu. However, career advancement opportunities need additional development to have significant impact on long-term commitment of the employees. This study offers valuable insights for hotel managers, human resource practitioners and policy makers to help them better their retention strategies by implementing effective human resource practices.